PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR : PERAN MODERASI MOTIVASI BELAJAR PADA MATA PELAJARAN EKONOMI - Shalsa Putri Azzahra; Edi Fitriana Afriza; Riky Rizki Junaidi (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Low student learning outcomes were found in grade X, where many scores did not meet the minimum passing criteria. The level of learning outcomes is influenced by several factors, including learning discipline and learning motivation. This study was conducted to determine the effect of learning discipline on learning outcomes with the moderating role of learning motivation in economics lessons in grade X at SMAN 1 Cihaurbeuti. This study used a survey research method with a quantitative approach, sampling technique using probability sampling by proportionate stratified sampling, and data analysis was performed through Moderate Regression Analysis (MRA) with a total of 206 participants. Based on the results of the study, it was found that study discipline had a significant positive effect on learning outcomes. Furthermore, learning motivation was proven to moderate the effect of study discipline on learning outcomes. The limitations of this study were that it was only conducted on one grade level, namely 10th grade students, so the results obtained did not reflect the overall condition. In addition, the respondents, who were students, did not fully understand the contents of the questionnaire, and many students answered the questions unseriously. This study implies the importance of strengthening learning discipline and learning motivation as factors that can improve student learning outcomes.